Standard-based inspection and teacher assessment of climbing facilities and equipment in pre-school and primary centers in the province of Pontevedra (Galicia) - Roberto Silva Piñeiro; David Pita Insua (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose was to identify the risks of climbing facilities in primary schools in the province of Pontevedra (Galicia) in comparison with the regulatory standard, as well as the teachers' assessment of their use, maintenance and safety. The study was carried out in 18 schools by means of an inspection check-list and a questionnaire. Bearing in mind that it is not common for climbing walls to be used for non-educational activities and by people other than the pupils themselves, the most frequent risks were the lack of signage and warnings, and it was found that all the facilities present some risk, of a trivial or tolerable level, which coincides with similar studies. It is important to provide the teaching staff with tools so that they can carry out periodic checks, although they confirmed that the climbing walls studied were totally safe for the activities carried out.